2001
DOI: 10.1093/jn/131.7.1993
|View full text |Cite
|
Sign up to set email alerts
|

The In Vivo Fate of Hydroxytyrosol and Tyrosol, Antioxidant Phenolic Constituents of Olive Oil, after Intravenous and Oral Dosing of Labeled Compounds to Rats

Abstract: In vitro studies have shown phenolics in olive oil to be strong radical scavengers. The absorption and elimination of two radiolabeled phenolic constituents of olive oil, hydroxytyrosol and tyrosol were studied in vivo using rats. Compounds were administered intravenously (in saline) and orally (in oil-and water-based solutions). For both compounds, the intravenously and orally administered oil-based dosings resulted in significantly greater elimination of the phenolics in urine within 24 h than the oral, aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(110 citation statements)
references
References 13 publications
(16 reference statements)
3
104
1
2
Order By: Relevance
“…We found 13 publications that addressed absorption, metabolism, or urinary excretion of olive oil phenols: five animal (Bai et al, 1998;Coni et al, 2000;D'Angelo et al, 2001;Tuck et al, 2001;Visioli et al, 2001), six human studies (Bonanome et al, 2000;Visioli et al, 2000a, b;Miro-Casas et al, 2001a, b;Vissers et al, 2002), and two studies that addressed characterisation of the metabolites of hydroxytyrosol in urine from two of the above-mentioned studies Tuck et al, 2002). One study by our group showed that apparent in vivo absorption of the ingested olive oil phenols was more than 55-66 mol% in humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 13 publications that addressed absorption, metabolism, or urinary excretion of olive oil phenols: five animal (Bai et al, 1998;Coni et al, 2000;D'Angelo et al, 2001;Tuck et al, 2001;Visioli et al, 2001), six human studies (Bonanome et al, 2000;Visioli et al, 2000a, b;Miro-Casas et al, 2001a, b;Vissers et al, 2002), and two studies that addressed characterisation of the metabolites of hydroxytyrosol in urine from two of the above-mentioned studies Tuck et al, 2002). One study by our group showed that apparent in vivo absorption of the ingested olive oil phenols was more than 55-66 mol% in humans.…”
Section: Resultsmentioning
confidence: 99%
“…One study by our group showed that apparent in vivo absorption of the ingested olive oil phenols was more than 55-66 mol% in humans. A study in rats showed that bioavailability of radiolabelled tyrosol and hydroxytyrosol was 71-99% compared to intravenously administered tyrosol and hydroxytyrosol (Tuck et al, 2001). Eight studies showed that of the total amount of ingested phenols, at least 5% was excreted in urine as tyrosol and hydroxytyrosol (Visioli et al, 2000a(Visioli et al, , b, 2001D'Angelo et al, 2001;Miro-Casas et al, 2001a, b;Tuck et al, 2001;Vissers et al, 2002), mainly as glucuronide (Visioli et al, 2000b;Miro-Casas et al, 2001a, b;Tuck et al, 2002) and monosulphate conjugates (D'Angelo et al, 2001;Tuck et al, 2002), and in the O-methylated form as homovanillic alcohol and homovanillic acid (Visioli et al, 2000a;Caruso et al, 2001;D'Angelo et al, 2001;Tuck et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In a later study, the same authors [59] noticed that the urinary levels of unconjugated tyrosol and hydroxytyrosol correlated with their intake, except at the highest dose, which increased the quantity of glucuronide conjugate. Tuck et al investigated the in vivo fate of hydroxytyrosol and tyrosol after intravenous and oral dosing of these tritium labelled compound to rats [60]. No significant differences in the amount of phenolic compounds eliminated in urine between the intravenous dosing method and the oral oil-based dosing method for either tyrosol or hydroxytyrosol were found.…”
Section: Health Aspects Linked To Phenols In Voomentioning
confidence: 99%
“…In all of the investigated tissues, Hyty was enzymatically converted in oxidized and/or methylated derivatives, whereas the major urinary products were sulfo-conjugates. Tuck et al (2001) compared the elimination of Hyty and Ty in rat urine within 24 h after administration, both orally (in oil-and water-based solutions) and intravenously (in saline). When orally administrated, polyphenols will be subjected to first-pass metabolism, so that the contribution of intestinal metabolism will be quite relevant.…”
Section: Absorption and Dispositionmentioning
confidence: 99%
“…This was supported by finding that 15% of an Ol glycoside supplement administered to healthy human subjects was excreted in urine as Hyty and Ty. Tuck et al (2001) investigated the in vivo fate of tritium labeled Hyty and Ty after intravenous (in saline, tail vein) and oral dosing (in oil-and water-based solutions) to rats. For both Hyty and Ty, the elimination of radioactivity in urine within 24 h for the intravenously and orally administered oil-based dosing was significantly greater (95 and 75%, respectively) than the oral aqueous dosing method (74 and 53%, respectively).…”
Section: Eliminationmentioning
confidence: 99%